The Effects of Stochastic Galvanic Vestibular Stimulation on Body Sway and Muscle Activity - Matsugi, Akiyoshi; Oku, Kosuke; Mori, Nobuhiko (Frontiers in Human Neuroscience, 2020)
[Objective] This study aimed to investigate whether galvanic vestibular stimulation with stochastic noise (nGVS) modulates the body sway and muscle activity of the lower limbs, depending on visual and somatosensory information from the foot using rubber-foam. [Methods] Seventeen healthy young adults participated in the study. Each subject maintained an upright standing position on a force plate with/without rubber-foam, with their eyes open/closed, to measure the position of their foot center of pressure. Thirty minutes after baseline measurements under four possible conditions (eyes open/closed with/without rubber-foam) performed without nGVS (intensity: 1 mA, duration: 40 s), the stimulation trials (sham-nGVS/real-nGVS) were conducted under the same conditions in random order, which were then repeated a week or more later. The total center of pressure (COP) path length movement (COP-TL) and COP movement velocity in the mediolateral (Vel-ML) and anteroposterior (Vel-AP) directions were recorded for 30 s during nGVS. Furthermore, electromyography activity of the right tibial anterior muscle and soleus muscle was recorded for the same time and analyzed. [Results] Three-way analysis of variance and post-hoc multiple comparison revealed a significant increment in COP-related parameters by nGVS, and a significant increment in soleus muscle activity on rubber. There was no significant effect of eye condition on any parameter. [Conclusions] During nGVS (1 mA), body sway and muscle activity in the lower limb may be increased depending not on the visual condition, but on the foot somatosensory condition.